Angels Everywhere : A Season of Angels and Touched by Angels - Books 1 & 3 - Macomber, Debbie (New York : Avon Books, 2002)
The haphazard angel team of Shirley, Goodness, and Mercy finds three special people who share Christmas dreams; then they respond to a Yuletide prayer request to teach a young woman a memorable lesson about life and love.
Keywords: Angels -- Fiction; Prayer -- Fiction; Christian fiction; Christmas stories; Love stories; Christian fiction; Christmas stories; Love stories